Plant analysis - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1987)
Plant analysis as a guide to the nutrient requirements of temperate and tropical crops / Martin-Prevel, P. et al. (eds.) (1987). Lavoisier Pub., Paris/New York, 744 pp.